Knowledge and Attitude of Patients Toward Hemorrhoids in Yogyakarta, Indonesia - Fadli Robby Amsriza; Rizka Fakhriani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Hemorrhoids are enlarged and displaced vascular structures located in the anal canal that may cause symptoms such as bleeding, pain, discomfort, and itching, thereby affecting patients’ quality of life. Although hemorrhoidal disease is common, evidence regarding knowledge and attitudes toward hemorrhoids in Indonesia remains limited. This study aimed to assess knowledge and attitudes regarding hemorrhoids among adults diagnosed with hemorrhoids in Yogyakarta, Indonesia. Methods: A cross-sectional study was conducted among adults aged ≥18 years diagnosed with hemorrhoids in Yogyakarta, Indonesia. Data were collected over six months using an online questionnaire adapted from previous studies. The questionnaire included demographic characteristics, 13 knowledge-related items regarding hemorrhoid definition, causes, complications, and preventive measures, as well as four questions assessing attitudes toward medical consultation and traditional medicine. SPSS version 24 was used to conduct descriptive statistics and chi-square analysis. Results: The study included 70 participants with 52.9% being male. Majority of the participants had awareness of common hemorrhoid symptoms particularly bleeding during defecation (98.6%) and dilated anal or rectal veins (88.6%). However, misconceptions were still observed with regard to complications and preventive measures including fiber-rich diet and adequate fluid intake. Overall, 65.7% of the participants were categorized as having good knowledge. In terms of attitudes, most of the participants reported willingness to seek medical consultation if hemorrhoidal symptoms occurred (94.3%) while 30% indicated preference toward traditional medicine. Cultural perceptions were also considered a potential barrier to medical consultation by 61.4% of the participants. Conclusion: Patients with hemorrhoids in Yogyakarta generally had good awareness of hemorrhoidal symptoms and positive attitudes towards seeking medical care. However, important misconceptions about prevention and complications were still found. These findings highlight the need for culturally sensitive educational interventions to improve public understanding of hemorrhoidal disease and to encourage timely medical consultation.